The demands of amputee soccer impair muscular endurance and power indices but not match physical performance - Simim, M. A.; da Mota, G. R.; Marocolo, M.; da Silva, B. V.; de Mello, M. T.; Bradley, P. S. (Adapted Physical Activity Quarterly, 2023)
We investigated the match demands (distances covered and acute physiological responses) of amputee soccer and its impact on muscular endurance and power. Measures such as heart rate, blood lactate concentration, subjective rating of perceived exertion, and time-motion characteristics were recorded in 16 Brazilian amputee soccer players during matches. Before and after matches, players completed a battery of tests: push-ups, countermovement vertical jump performance, and medicine ball throwing. Small differences were found between the first and second half for the distance covered in total and across various speed categories. Heart rate responses, blood lactate concentrations, and peak speed did not differ between halves, and all neuromuscular performance measures decreased after the match particularly after push-ups, although the rating of perceived exertion increased markedly compared with prematches. Although match physical performances were consistent across halves, the overall demands impaired test performance, especially for upper limb and closed kinetic chain exercise.